Utilization of the Thermoelectric Sensor to Realize a New Fluid Level Detector - K. Hachami; D. Moussaid; M. Rahmoun; E. Bendada (Active and Passive Electronic Components)
This paper describes a prototype thermoelectric sensor system which makes use of the thermoelectrical effects. The sensor includes two printed circuits, the first is constituted of a resistive constantan track, the second is a planar thermoelectric circuit constituted of many plated differential thermocouples. The first circuit is placed at the top of the second circuit so that the resistive tack is placed on the top of the even thermocouple junctions. The measuring method consists to passing an electrical current through the constantan track in order to generate temperature gradients between the junction points of the second circuit. Then the resulting temperature differences between the junction points is directly converted into a proportional Seebeck voltage. As an application, the sensor is placed into a reservoir and adapted in order to realize a fluid level detector.